2022
DOI: 10.3897/folmed.64.e67475
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of indocyanine-mediated photodynamic therapy cytotoxicity in human osteoblast-like cells: an in vitro study

Abstract: Introduction: Antimicrobial photodynamic therapy (aPDT) is an adjunctive non-invasive procedure for the management of periodontal tissue infection and deep periodontal pocket decontamination. However, the effects of this procedure on periodontal cells like osteoblasts that play a role in periodontal tissue repair and regeneration is not yet clear. Aim: This study aimed to investigate aPDT based on indocyanine green (ICG) on MG-63 osteoblast-like cells in vitro. Materials and methods: MG-63 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 22 publications
1
0
0
Order By: Relevance
“…In the present study, aPDT with 808 nm diode laser and ICG caused a significant reduction in the E faecalis count, which is in consistent with the results of most studies conducted on the efficacy of aPDT with ICG on E. faecalis elimination [21,22]. A study has also shown that there is no evidence of cytotoxicity of ICG to MG-63 human osteoblast-like cells [23]. Furthermore, the results of this study show that ICG + SWEEPS has significant efficacy in removing E. faecalis biofilms compared to the control (p < 0.001).…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, aPDT with 808 nm diode laser and ICG caused a significant reduction in the E faecalis count, which is in consistent with the results of most studies conducted on the efficacy of aPDT with ICG on E. faecalis elimination [21,22]. A study has also shown that there is no evidence of cytotoxicity of ICG to MG-63 human osteoblast-like cells [23]. Furthermore, the results of this study show that ICG + SWEEPS has significant efficacy in removing E. faecalis biofilms compared to the control (p < 0.001).…”
Section: Discussionsupporting
confidence: 92%